PERANCANGAN SISTEM INFORMASI STOK OBAT PADA APOTEK METROMEDICA CENTER JAKARTA - Yasin, Muhammad; Sutriyadi, Riko (JURNAL LENTERA ICT, 2018)
Apotek Metromedica Center is a private institution engaged in the pharmaceutical sector located on Jalan Pejaten Raya, South Jakarta. This pharmacy still requires a drug stock system in order to create time efficiency and data accuracy. The drug stock process at the Metromedica Center Pharmacy still does not use a computer system. Employees in recording drug stock must write incoming and outgoing stock data on sheets of paper, then in making reports of incoming and outgoing drug stocks written in the report book. Keywords: system design, stock, medicine